Breakdown of Ergodicity in Isolated Quantum Systems: From Glassiness to Localization - AAVV, AAVV (Il Colle di Galileo, 2021)
We report on a workshop, held at GGI, in which researchers from several universities and research centers around the world met to discuss recent breakthroughs in our understanding of the approach to thermal equilibrium of quantum systems. The discussion spanned from the fundamental problems concerning the interplay of the foundations of thermodynamics and quantum mechanics, to the implications for quantum technologies, in particular for quantum computing.